Eliptyczne funkcje łączące - Heilpern, Stanisław (Elliptical copulas, 2007)
The paper is devoted to the elliptical copulas. These copulas are generated by the elliptical distributions. The main properties of the elliptical copulas are presented. The characteristic properties, which are distinguishable from other copulas, mainly Archimedean, are emphasized. The basic types of the elliptical distributions, the elliptical copulas: Gaussian and Student, their identification, the problem of simulation and the direction of generalization are discussed.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1189, s. 60-71